Metode Cepat Membaca Al-Qur’an di Yayasan Miftahul Ulum Kecamatan Lenteng Kabupaten Sumenep - Khairul Muttaqin; Jamal Abd. Nasir; Moh Subhan Zamzami (IAIN Madura, 2019)
Reading the Qur'an smoothly and correctly is a necessity and necessity for all Muslim communities in the world. Why not, the Holy Qur'an which is believed by Muslim communities throughout the world can be read only by understanding the rules of recitation, the letter, the character of letters and practicing repeatedly. The group that is the target of community service activities is the female students of the Islamic Boarding School of Miftahul Ulum Sumenep. The target group does not yet have the knowledge and skills to read the Qur'an in accordance with the rules of recitation, the letters of letters and the character of letters. For this reason, in the community service activities, material will be conveyed about the rules of recitation, letters and letters and practice them repeatedly. The repeated training was held at the mosque of the Islamic Boarding School of Miftahul Ulum Sumenep. As a result, the female students of the Islamic Boarding School of Miftahul Ulum in Sumenep finally gained in-depth knowledge about the rules of recitation, letters and letters and could practice it and avoid mistakes in reading the Qur'an.